O ensino da gramática através da leitura: uma experiência com Monteiro Lobato - SILVA, Elzenira Benedita Macêdo da (2024)
This study aimed to verify the possibility to develop a teaching-learning process using the "Emilia no País da Gramática" of Monteiro Lobato through a study applied research sub-jects with the students of the 6th year of primary and secondary Education School Professor Basil of oak, located in the city of Abaetetuba.First came a bibliographic analysis about the author and his work. Took as theoretical assumptions for analysis of grammatical elements the New Contemporary Portuguese Grammar of wedge Cunha and Cintra (2008). It was used also as a point of support, the signs of Coutinho (1978) on the literary aspects of the work. In the analysis of Lobatiana composition, were studied four chapters: "Important People and poor people,"; "In the sea of nouns"; "Between the Adjectives" and "articles and numerals" during intervention with students, and while reading applied learning scanning activities. The results pointed to the statement that the work in question is an innovative practice of teaching and learning the operation of the Portuguese Language.